2016
DOI: 10.1515/hmbci-2016-0035
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter alteration in a testosterone propionate-induced polycystic ovarian syndrome rat model

Abstract: Neurotransmitter alteration could be one of the reasons for disturbed gonadotropin-releasing hormone (GnRH) release, consequently directing the ovarian dysfunction in PCOS. Also, decrease in neurotransmitters, mainly NE, serotonin and dopamine (DA) attributes to mood disorders like depression and anxiety in PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…However, there was a significant troxerutin-caused (300 mg/kg) decline in hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5~3 mIU/ml [34,35], FSH levels varied from 8mIU/ml to 20mIU/ml [26,36] and testosterone varied from 0.2 to 10 ng/ml [34,[36][37][38][39], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was a significant troxerutin-caused (300 mg/kg) decline in hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5~3 mIU/ml [34,35], FSH levels varied from 8mIU/ml to 20mIU/ml [26,36] and testosterone varied from 0.2 to 10 ng/ml [34,[36][37][38][39], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was a significant troxerutin-caused ( 300 mg/kg) decline in serum and hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5 ~ 3 mIU/ml [32,33], FSH levels varied from 8mIU/ml to 20mIU/ml [22,34]and testosterone varied from 0.2 to 10 ng/ml [32,[34][35][36][37], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Possession Of Beneficial Effects On Animal Models Of Differesupporting
confidence: 91%
“…However, the concentration and duration of letrozole treatment in that study was much higher as compared to our study. Furthermore, the possibility that the currently observed changes in neurotransmitters are due to other interactions of letrozole can be ruled out by our previous study wherein testosterone propionate-induced PCOS rat model also demonstrated similar neurotransmitter profile [ 67 ]. This thereby strengthens the result of present study indicating that neurotransmitter modulation is a pivotal attribute of PCOS condition.…”
Section: Discussionmentioning
confidence: 99%